Wall teichoic acid-dependent phagocytosis of intact cell walls of Lactiplantibacillus plantarum elicits IL-12 secretion from macrophages - Kojima, Naoya; Kojima, Shohei; Hosokawa, Shin; Oda, Yoshiki; Zenke, Daisuke; Toura, Yuta; Onohara, Emi; Yokota, Shin-ichi; Nagaoka, Masato; Kuroda, Yasuhiro (Frontiers in Microbiology, 2022)
Selected lactic acid bacteria can stimulate macrophages and dendritic cells to secrete IL-12, which plays a key role in activating innate and cellular immunity. In this study, we investigated the roles of cell wall teichoic acids (WTAs) displayed on whole intact cell walls (ICWs) of Lactiplantibacillus plantarum in activation of mouse macrophages. ICWs were prepared from whole bacterial cells of several lactobacilli without physical disruption, and thus retaining the overall shapes of the bacteria. WTA-displaying ICWs of several L. plantarum strains, but not WTA-lacking ICWs of strains of other lactobacilli, elicited IL-12 secretion from mouse bone marrow-derived macrophages (BMMs) and mouse macrophage-like J774.1 cells. The ability of the ICWs of L. plantarum to induce IL-12 secretion was abolished by selective chemical elimination of WTAs from ICWs, but was preserved by selective removal of cell wall glycopolymers other than WTAs. BMMs prepared from TLR2- or TLR4-deficient mouse could secret IL-12 upon stimulation with ICWs of L. plantarum and a MyD88 dimerization inhibitor did not affect ICW-mediated IL-12 secretion. WTA-displaying ICWs, but not WTA-lacking ICWs, were ingested in the cells within 30 min. Treatment with inhibitors of actin polymerization abolished IL-12 secretion in response to ICW stimulation and diminished ingestion of ICWs. When overall shapes of ICWs of L. plantarum were physically disrupted, the disrupted ICWs (DCWs) failed to induce IL-12 secretion. However, DCWs and soluble WTAs inhibited ICW-mediated IL-12 secretion from macrophages. Taken together, these results show that WTA-displaying ICWs of L. plantarum can elicit IL-12 production from macrophages via actin-dependent phagocytosis but TLR2 signaling axis independent pathway. WTAs displayed on ICWs are key molecules in the elicitation of IL-12 secretion, and the sizes and shapes of the ICWs have an impact on actin remodeling and subsequent IL-12 production.